Collapsing Glomerulopathy in Portugal: a Review of the Histological and Clinical Findings in HIV and Non-HIV Patients - Ferreira, AC (2018)
BACKGROUND: Collapsing glomerulopathy (CG) is a glomerulonephritis seen in association with human immunodeficiency virus (HIV) infection, known as HIV-associated nephropathy (HIVAN), and less frequently observed in non-HIV-infected patients. Method. The aim of this study was to review the histological and clinical findings of all CG diagnosed since 1981 in our laboratory. Result. Since 1981, 18 kidney biopsies with collapsing features were diagnosed among 6130 biopsies performed: 72.2% (n = 13) males, mean age 33.8 ± 9.7 years, 61.1% (n = 11) of black ethnic origin. HIV infection was present in 10 patients. Mean serum creatinine (Scr) was 4.7 ± 2.5 mg/dL, and mean proteinuria was 6.1 ± 5 g/24 h. Both HIVAN and non-HIVAN patients were similar in terms of age, gender and dialysis requirement. In the HIVAN population, African origin was predominant and more frequent than in the non-HIVAN population, Scr was higher and proteinuria was less severe. Interstitial infiltrate, interstitial fibrosis and tubular atrophy were severe, and the presence of microcystic dilatation of renal tubules was more common. Immunofluorescence was positive in six patients. In the non-HIVAN population, this histological lesion was related to an infectious illness in 6/8 patients and to the use of illegal oral drugs in one patient. Interstitial infiltrate, interstitial fibrosis and tubular atrophy presented as moderate to severe, and tubular atrophy correlated with dialysis requirement. Mesangial proliferation was present in 3/8 patients, with C3 and IgA deposits. CONCLUSION: CG is a rare podocytopathy. In this study, the association between infection and CG is evident, and we may suggest that infections could, in a direct or indirect manner, be a trigger of podocyte injury.